The Correlation Of Excessive Assignment Between Student’s Mental Health - Abdul Syahid; Winna Winna; Iffa Kharimah; Lafifah Sulliya; Yeni Suryani; Refi Komariah; Putri Sulastri Permata Sari (Jurnal Ilmu Pendidikan Nasional (JIPNAS), 2023)
This research investigated the correlation of excessive assignments on the mental health of fifth-year English language students at State Islamic Religious Institution in Central Kalimantan. The research hypothesized a strong positive correlation between perceived assignment load and mental health problems. The method of this research used quantitative approach using a questionnaire. The Data was collected from 20 participants. The researchers, analyzed the data using pearson's correlation coefficient JASP to examine the relationship between excessive assignment and mental health condition. Based on the findings, the result showed a significant positive correlation (r = 0.900, p <.001) between excessive assignment and mental health condition, indicating that 81.0% of the variance in students' mental health could be attributed to their perceived workload. Educational institutions should take proactive steps to manage student workloads and provide mental health support services, such as counseling, time management training, and flexible deadlines. Promoting a balanced approach to academic assessment that prioritizes both academic excellence and student well-being is crucial for fostering the success and well-being of English language students. This research limited due to the small sample size and focus on a specific student population. Future research with larger and more diverse samples is needed to further explore the complex relationship between academic demands and student mental health. The findings highlight the urgent need for universities and educators to prioritize student mental health alongside academic achievement. Implementing practical strategies to manage workloads and provide mental health support can promote a more holistic and student-centered educational environment.